THE EFFECT OF EDUCATION, HEALTH, UNEMPLOYMENT AND DISTRIBUTION OF ZAKAT TO POVERTY IN YOGYAKARTA - Prasojo, Prasojo; Khorunisa, Isnaini (I-Economics, 2020)
Poverty is a big problem of economic development in a developing country. Many indicators can cause poverty. The research aims to examine the influence of education, health, unemployment and zakat towards the poverty in the special region of Yogyakarta from 2011 to 2016. The panel data regression with random effect models that are taken by the test Chow and Hausman test were applied for performing a hypothesis test. The data analysis using E-views 8 program. The results found that education and unemployment positively influence poverty. The health and zakat negatively influence poverty. Partially education and health are not significant. Unemployment and zakat significantly influence poverty.